Investment in Schooling and the Marriage Market - Chiappori, Pierre-André; Iyigun, Murat; Weiss, Yoram (American Economic Review, 2009)
We present a model in which investment in schooling generates two kinds of returns: the labor-market return, resulting from higher wages, and a marriage-market return, defined as the impact of schooling on the marital surplus share one can extract. Men and women may have different incentives to invest in schooling because of different market wages or household roles. This asymmetry can yield a mixed equilibrium with some educated individuals marrying uneducated spouses. When the labor-market return to schooling rises, home production demands less time, and the traditional spousal labor division norms weaken, more women may invest in schooling than men. (JEL I21, J12, J24, J31)